Cationized Natural Dyeing of Cotton Fabrics with Corn Poppy (Papaver rhoeas) and Investigation of Antibacterial Activity - Gedik, Gorkem; Yavas, Arzu; Avinc, Ozan; Simsek, Omer (Asian Journal of Chemistry, 2013)
In this study, cotton fabrics were dyed with Papaver rhoeas flowers (petals) in company with four different mordant chemicals via pre-mordanting method. The effect of cationizing was investigated. Colorimetric properties, colour fastness (wash, alkali and acid perspiration, wet and dry rub and light fastness) values and antibacterial activity were determined after different process sequence combinations of cationizing, mordanting and dyeing. Different shades of green, brown, lead and tan colours were obtained on cotton fiber dyed with papaver rhoeas flowers. Cationizing process increased the colour yield on both un-mordanted and mordanted samples. Sequential application of cationizing then dyeing resulted in significantly higher colour yield value than simultaneous application of cationizing and dyeing. The application of a cationizing agent together with a mordant material at the pre-mordanting step then dyeing caused the highest colour values on cotton fiber. The highest colour yield and chroma values on cotton fiber were observed after process combinations of simultaneous cationizing and mordanting with copper(II) sulphate then dyeing process. Cotton dyeing with Papaver rhoeas exhibited outstanding wash fastness results. Moreover, perspiration and dry rub fastness values were generally in the commercially acceptable range. There is no clear trend that the processes sequence of cationizing, mordanting and dyeing affects the studied colour fastness properties significantly. Cationization increased the inhibitory activity of mordants. Application sequence of cationizing then mordanting then dyeing processes, for each mordant material, resulted in better antibacterial activity leading to higher reduction on E. coli. The highest antimicrobial activity (72 % reduction) was obtained in the treatment of cationizing then mordanting with copper(II) sulphate then dyeing.